THE CRIMINAL INVESTIGATION PROCESS OF THE CRIMINAL INVESTIGATION UNIT ON DISCLOSURE THE THEFT BY WEIGHTING TO INCREASE CRIME CLEARANCE IN POLRES SUKOHARJO - MUHAMAD TEGAR ANDRIZALA ANDRIZALA (Police Studies Review, 2022)
This research is motivated by the Chief of Indonesian Police’s priority program, the first and the second PRESISI, namely predictive and responsibility. In respond to that program, the Sukoharjo Police Criminal Investigation Unit must be predictive and responsibility on the investigation process of the theft by weighting. However, since 2016 untill now the crime clearance of the theft by weighting hasn’t improved. Therefore, a study was conducted that aims to determine the investigation efforts of the Sukoharjo Police Criminal Investigation Unit in disclosing the crime of stealing, the factors that influence, and the cause of the decrease in the number of case settlements. The knife of analysis in this research is management theory and achievement motivation theory which is carried out using a qualitative approach with the type of research that is descriptive qualitative to explain phenomena that occur in the field. As well as data collection techniques by conducting interviews, observations, and document review. The results of the study found that efforts to investigate the crime of stealing were influenced by both internal and external factors. Investigation efforts carried out by the Sukoharjo Police criminal investigation unit still use the general method of investigation that is guided by Perkap number 6 of 2019 concerning investigation. The absence of the use of technology that is already owned by the National Police has resulted in no increase in case disclosure, as well as the accumulation of unresolved cases that have contributed to the decline in crime clearance at the Sukoharjo Police. Based on the results of the study, the authors suggest reforms in the criminal investigation process by utilizing the technology currently available by the National Police such as cell dump and direction finder and by establishing information networks in collaboration with informants, both the community and former perpetrators of theft by weight.